Idelalisib in a patient with refractory Waldenström’s macroglobulinemia complicated by anuric renal failure: a case report - D’Aveni-Piney, M. (J Med Case Rep, 2018)
BACKGROUND: Waldenström’s macroglobulinemia is a rare B-cell lymphoma. The gold standard treatment for Waldenström’s macroglobulinemia is an anti-CD20 antibody (rituximab) in combination with alkylating agents and dexamethasone. Treatment targeting the B-cell receptor such as ibrutinib (but not idelalisib) is currently approved for treatment of patients with relapsed or refractory Waldenström’s macroglobulinemia. CASE PRESENTATION: We report a case of a 71-year-old white French man with Waldenström’s macroglobulinemia who presented with acute renal failure and hyperviscosity syndrome. His Waldenström’s macroglobulinemia was refractory to first-line treatment with rituximab, cyclophosphamide, and dexamethasone. Because of his hemorrhagic syndrome and medical history of recent myocardial infarction, we decided to treat him with idelalisib 150 mg twice daily instead of ibrutinib. We observed a very quick improvement in the patient’s clinical status without need for dose adjustment. CONCLUSION: Our patient’s case provides the first evidence, to the best of our knowledge, that idelalisib may be an efficient treatment option for patients with Waldenström’s macroglobulinemia complicated by anuric renal failure and in whom ibrutinib is contraindicated.